2019
DOI: 10.18410/jebmh/2019/84
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Tympanoplasty Versus Endoscopic Tympanoplasty: A Comparative Study in a Tertiary Care Centre of West Bengal

Abstract: BACKGROUND Chronic otitis media is one of the most common health problems of our country. Perforation in their tympanic membrane and hearing loss are the presenting feature of chronic otitis media. Reconstruction of the hearing mechanism can be done by surgical procedure namely tympanoplasty. This study is being conducted to compare the success rate of tympanoplasty regarding graft uptake, hearing improvement and also to assess the advantage and disadvantage of endoscope and microscope during surgery. MATERIAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…12 A study published recently in 2019 revealed that graft success rate in endoscopic tympanoplasty is 86.66% whereas in microscopic tympanoplasty, it was 83.33%. 13 Another study reported that pre-operated mean air conduction was 53.22 + 12.24dB, post-operated mean air conduction was 39.11 + 19.93dB and post-operated AB-gap decreased by 8.68dB. 14 this study also co relate with our study.…”
Section: Discussionsupporting
confidence: 88%
“…12 A study published recently in 2019 revealed that graft success rate in endoscopic tympanoplasty is 86.66% whereas in microscopic tympanoplasty, it was 83.33%. 13 Another study reported that pre-operated mean air conduction was 53.22 + 12.24dB, post-operated mean air conduction was 39.11 + 19.93dB and post-operated AB-gap decreased by 8.68dB. 14 this study also co relate with our study.…”
Section: Discussionsupporting
confidence: 88%